1976
DOI: 10.1016/s0006-3495(76)85749-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation-inactivation coupling in Myxicola giant axons injected with tetraethylammonium

Abstract: Myxicola giant axons internally injected with tetraethylammonium chloride to block potassium currents were examined under voltage clamp. The sodium inactivation time constants obtained from the decline in INa during step depolarizations were substantially smaller than those obtained using conditioning prepulses to the same potentials and the ratios agreed with previous observations using TTX. Inactivation shifts were also measured and found to be comparable to previous results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…Block of the residual 'K occurs more slowly over the next 3-5 min. Voltage clamp records obtained before and 30 min after internal application of TEA+ show that with 40 mM-TEA+ IK is completely eliminated at potentials more negative than + 30 mV, but some residual 1K remains at very large potentials as was observed in intact axons injected with TEA+ (Schauf, Pencek & Davis, 1976a).…”
Section: Asymmetry Currents In Dialysed Myxicolamentioning
confidence: 67%
See 2 more Smart Citations
“…Block of the residual 'K occurs more slowly over the next 3-5 min. Voltage clamp records obtained before and 30 min after internal application of TEA+ show that with 40 mM-TEA+ IK is completely eliminated at potentials more negative than + 30 mV, but some residual 1K remains at very large potentials as was observed in intact axons injected with TEA+ (Schauf, Pencek & Davis, 1976a).…”
Section: Asymmetry Currents In Dialysed Myxicolamentioning
confidence: 67%
“…It has been suggested that sodium activation and inactivation in Myxicola cannot be described as independent first-order processes because the time constant of prepulse inactivation (rE) is much larger than the time constant of inactivation 312 ASYMMETRY CURRENTS IN DIAL YSED MYXICOLA (T4) during a maintained depolarization (Goldman & Schauf, 1973;Schauf & Davis, 1975). This difference was shown in Myxicola axons injected with TEA+ and treated with tetrodotoxin (TTX) to reduce INa by up to 80 % to reduce or eliminate errors due to imperfect leak substraction or inadequate compenation for membrane series resistance (Schauf et al 1976a). However, its existence in squid axons is a matter of dispute .…”
Section: Activation-inactivation Coupling In Dialysed Axonsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not seem to have been a significant problem. Schauf et al (1976) repeated the "rc-~'h determinations in Myxicola axons injected with tetraethylammonium ions so as to reduce substantially the K current (Armstrong and Binstock, 1965), and assumed a linear leak correction. Subtractions were then not needed to extract the Isa-Their results were identical to those of Goldman and Schauf (1973).…”
Section: Experiments With Low Na Currentsmentioning
confidence: 99%
“…Rather, the voltage dependence of inactivation may arise from some 'coupling' to the activation process (Hoyt, 1965). Experimental evidence for this point of view has been obtained both from studies of the kinetics of sodium currents (Goldman & Schauf, 1972, 1973 Schauf, Pencek & Davis, 1976b;, and from the time course of membrane asymmetry ('gating') currents and the manner in which they vary with increasing pulse duration . A detailed kinetic model for C. L. SCHAUF AND K. J. SMITH such a process has been developed based on the existence of a physiological 'inactivating particle' which can enter and block the Na+ channel from the interior of the cell Armstrong & Gilly, 1979).…”
Section: Introductionmentioning
confidence: 99%